Analisis Peran Gender dalam Pengelolaan Kawasan Hutan Dengan Tujuan Khusus Sisimeni Sanam - Khofifah Eta Parera; Mamie E. Pellondo’u; Astin E. Mau (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2023)
Forest management that involves both men and women will provide enormous benefits in forest management policy. Equal division of roles certainly underlies the agreement between the two, but it is not optimal because it is influenced by several factors that result in differences of opinion, where men dominate roles that are far more important and diverse. The purpose of this study was to determine the time allocation of gender division of labor and analyze the roles of men and women in decision-making in forest management activities. This research was conducted from February to March 2022 in KHDTK Sisimeni Sanam (KTH Paloil Tob, KTH Tunas Baru, KTH Feanbol) Silu Village, Kupang Regency. The object of this study were farmers of KTH Paloil Tob, KTH Tunas Baru, and KTH Feanbol with 30 respondents with each in each KTH taken 5 women and 5 men. Data collection techniques were carried out by direct observation and direct communication guided by a draft interview in the field. The results showed that the role of gender in the outlay of work time by members of KTH there, men play a greater role than women in forest management or productive activities in Silu Village, namely the outlay of work time of 6.4 HOK / year and women of 3.6 HOK / year. Meanwhile, decision-making in forest management is dominated by men.